The Awaete-Parakanã people resistences (to existences) in the construction of a specific and differentiated school education - Maria Cristina Macedo Alencar; Laécio Rocha de Sena; Mayane Lima Nonato (Universidade Federal do Norte do Tocantins, 2022)
In this work we thought over about the school appropriation processes by the Awaete-Parakanã People, in the indigenous land Parakanã, located in the town of Novo Repartimento - PA. It was aimed here to understand the historical relationship of the Awaete-Parakanã with the school and, more recently, developed the main role in the process of school appropriation in their territory, in view of the theoretical perspective of Baniwa (2006). For this work is analyzed a literature was carried out on the policies of the Brazilian state that forced contact with indigenous peoples, focusing on the history of the Awaete-Parakanã. Studies already produced on indigenous school education policies in Brazil were also analyzed (Baniwa (2006), Fernandes (2010), Cohn (2016), Alencar (2018), Faustino (2006), Emídio-Silva (2017)). It was observed the Awaete-Parakanã People has reframed the school role in their territory, since they have a very clear school project and how the school should work towards their future project as ethnic group.